Developmental changes in proton MR spectroscopy of the brain - Hashimoto, T; Tayama, M; Miyazaki, M; Fujii, E; Harada, M; Miyoshi, H; Tanouchi, M; Kuroda, Y (No to hattatsu, 1994)
Volume-selective proton MR spectroscopy (1H-MRS) of the brain was performed on a 1.5 T magnet in 31 healthy children aged from 1 month to 15 years and one healthy adult. Peaks of N-acetylaspartate (NAA), choline (Cho) and creatine (Cr) were observed in all cases on 1H-MRS, but not lactate. On 1H-MRS of the right parietal region, with advancing age, 1H-MRS revealed an increase in the ratios of NAA to Cho and NAA to Cr and a decrease in Cho to Cr. The most rapid change was noted during the first one to three years of life. 1H-MRS of the right frontal region was also performed in eleven cases. The ratio of NAA/Cho was smaller in the right frontal region than in the right parietal region. From this result, it may be suggested that the neuronal maturation in the frontal region delays as compared with the parietal region.